Design of oral agents for the management of multiple sclerosis: benefit and risk assessment for dimethyl fumarate - Nicholas JA; Boster AL; Imitola J; O'Connell C; Racke MK (Dove Medical Press, 2014)
Jacqueline Ann Nicholas,1 Aaron Lee Boster,1 Jaime Imitola,1,2 Colleen O’Connell,1 Michael Karl Racke1,21Department of Neurology and Multiple Sclerosis Center, 2Department of Neuroscience, The Ohio State University, Columbus, OH, USAAbstract: Dimethyl fumarate (DMF) is the most recent oral disease-modifying therapy approved by the US Food and Drug Administration and is indicated for the treatment of relapsing forms of multiple sclerosis (MS). Prior to approval for use in MS, DMF and its active metabolite, monomethyl fumarate, had been used for decades as two of the fumaric acid esters in Fumaderm®, a medication used in Europe for the treatment of psoriasis. The unique mechanism of action of DMF remains under evaluation; however, it has been shown to act through multiple pathways leading to shifts away from the Th1 proinflammatory response to the less inflammatory Th2 response. Preliminary data suggest that DMF may induce neuroprotective effects in central nervous system white matter, although further studies are needed to demonstrate these effects on inflammatory demyelination. The DMF Phase III clinical trials demonstrated its efficacy with regard to a reduction in the annualized relapse rate and reductions in new or enlarging T2 lesions and numbers of gadolinium-enhancing lesions on magnetic resonance imaging. DMF has a well-defined safety profile, given the experience with its use in the treatment of psoriasis, and more recently from the DMF clinical trials program and post-marketing era for treatment of MS. The safety profile and oral mode of administration of DMF place it as an attractive first-line therapy option for the treatment of relapsing forms of MS. Long-term observational studies will be needed to determine the effects of DMF on progression of disability in MS.Keywords: multiple sclerosis, dimethyl fumarate, disease-modifying therapy, Nrf2 pathway, quality of life